Long-run effects of early childhood exposure to cholera on final height: Evidence from industrializing Japan - Kota Ogasawara; Tatsuki Inoue (Elsevier, 2018)
Pandemic cholera is one of the most topical and urgent issues in many developing countries. However, although a growing body of research has shown the negative long-run effects of infectious disease exposure on human health, the long-run influences of early childhood exposure to cholera have thus far been understudied. To bridge this gap in the body of knowledge, we draw both on new data describing adult height from 1899 to 1910 from comprehensive official Japanese army records and on data recording the regional variation in the intensity of cholera pandemics. By using a difference-in-differences estimation strategy, we find that exposure to pandemic cholera had stunting effects on the final height of men at that time. Our estimates also suggest that early-infancy exposure to cholera seems to have a stronger long-run effect on adult height than late-infancy exposure. JEL: I19, Keywords: Early-life health, Fetal origins, Pandemic cholera, Height, Long-run effect